Case Study: User satisfaction on Human Resource Management Information System (HRMIS) in Terengganu Police Contingent Headquarters (IPK Terengganu) - Harun, Mohd Amir (2016)
HRMIS is known as the Malaysian government’s effort to ensure that human resource management in the Public Service will produce skilled, trained and motivated workers. The project was developed based on six key principles aimed at realizing the K-economy. HRMIS objective is to enable a competent management resource enhanced by the modernization of technology-based for a better and condusive working environment. The implementation of HRMIS so-called system evolved in line with the Electronic Government (E-government) agenda; where the project is anchored by the Public Service Department (PSD) started in 1999. Studies show that failure of Information System (IS) duly because of psychological/organizational issues; comparable to technology issues during development and implementation stages (Garrity & Sanders, 1998). Public Service Department (PSD) of Malaysia and Malaysian Administrative Modernization and Management Planning Unit (MAMPU) on March 2012 had been given the task to re-develop and solve the dissatisfaction among public service servant on HRMIS2 system. According to Eghrmis (2012), essential actions had been taken to solve dispute among HRMIS faulty and errors to ensure the longevity of HRMIS application within government servant. Thus, the main objective of this proposal is to investigate and identify on user satisfaction among users (government servant in IPK Terengganu) towards HRMIS application. Measuring employee’s satisfaction and technology acceptance is a must for identifying the acceptance and satisfaction of Terengganu Police Contingent Headquarters (IPK Terengganu) employees on managing HRMIS system to compute information regarding routine tasks. Overall findings of this research show that HRMIS application, user's characteristic and also organizational supports are positively related towards user's satisfaction among HRMIS users in IPK Terengganu. Based on the output gathered from the SPSS system, the researcher would like to give some recommendation for future enhancement.